PENGARUH PENYULUHAN PAJAK DAN PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN KONSULTAN PAJAK SEBAGAI VARIABEL MODERASI PADA KPP PRATAMA MEDAN BELAWAN - Tina, Agus (Jurnal Akuntansi Kompetif, 2024)
This research aims to determinate, test and analyze empirically regarding tax counseling and tax audits regarding individual taxpayer compliance which is moderated by tax consultants at KPP Pratama Medan Belawan. This type of research is quantitative research with an associative approach. The object of this research is individual taxpayers registered with KPP Pratama Medan Belawan. The sampling technique used in this research is stratified random sampling with a sample size of 100 respondents from a total population in 2020 of 167,250 respondents. The data collection technique is carried out by distributing questionnaires. Meanwhile, the data analysis technique is to use the structural equation model partial least squares (SEM-PLS) which is processed using Smart PLS statistical software. The results of this research show that Tax Counseling has an effect on individual taxpayer compliance at KPP Pratama Medan Belawan. Tax Consultants are able to moderate the influence of tax counseling on individual taxpayer compliance at KPP Pratama Medan Belawan. Tax audits have no effect on individual taxpayer compliance with KPP Pratama Medan Belawan. Tax consultants are unable to moderate the influence of tax audits on individual taxpayer compliance at KPP Pratama Medan Belawan